O conflito trabalho-família vivenciado por mulheres empreendedoras do setor de confecção - Bandeira, Emanuella Lustosa (2017)
The interface between work and family has attracted the attention of several researchers, especially since the insertion of women into the labor market, when work-family conflicts have increased considerably. In an attempt to soften some of these conflicts, women have been using alternative strategies to formal and inflexible jobs, among which entrepreneurship stands out. However, Brazilian researches that relate female entrepreneurship and the interaction between family and professional life are still very scarce, while international literature has been focusing on this topic since the 1970s. In this sense, this research aims to analyze the work-family conflicts experienced by women entrepreneurs of the state of Ceará, characterizing those conflicts in the dimensions of time, tension and behavior, according to the multidimensional model proposed by Greenhaus and Beutell (1985). In addition, it seeks to identify the initial motivations to undertake, as well as the strategies used to attenuate conflicts, as indicated by Shelton (2006). This research is characterized as qualitative, descriptive, carried out through semi-structured interviews with 9 women entrepreneurs who work in the clothing sector. The primary data collected are treated through the content analysis and operationalized in the software ATLAS.ti 7. The results indicate that the most incidental conflicts are related to the excessive workload, which implies in a short time dedicated to the entrepreneur and self-demand for participation in the family; the main motivation to become a entrepreneur is the identification of market opportunity; in the dimension of time, tension and behavior, the predominant conflicts are: responsibility and involvement with work, expectations of business expansion and incompatibility of roles; and the main attenuation strategy is the sharing of both domestic and professional activities. Finally, the study suggests to the government to implement public policies that promote female entrepreneurship, which can provide national growth and economic development, as well as the deepening of emerging issues, such as maternity and financial returns.